Health economic evaluations of medical devices in the People's Republic of China: A systematic literature review - Zhang R; Modaresi F; Borisenko O (Dove Medical Press, 2015)
Rongrong Zhang, Farhang Modaresi, Oleg Borisenko Synergus AB, Stockholm, Sweden Background: The objective of this study is to identify and review the methodological quality of health economic evaluations of medical devices performed in the People's Republic of China. To our knowledge, no such investigations have been performed to date. Methods: A systematic literature review involving searches of Medline, Medline In-Process, the National Health Service Economic Evaluation Database, the Cost-Effectiveness Analysis Registry of the Tufts Medical Center, and the Wanfang Database was performed. The search spanned the period from 1990 to 2013. Studies on health economic evaluations of medical devices, in-vitro diagnostics, procedures, and the use of medical devices in Chinese health care settings were included. Full-text articles and conference abstracts in English and Chinese were included. Results: Fifty-seven publications were included, 26 (46%) of which were in English and 31 (54%) of which were in Chinese. The included publications covered a wide range of clinical areas, such as surgery (n=23, 40%), screening (n=9, 16%), imaging use (n=6, 11%), kidney intervention (n=4, 7%), and nine other technological areas. Most of the studies (n=31, 54%) were cost analyses. Among the others, 13 (50%) studies used modeling, and another 13 (50%) were within-trial evaluations. Among studies that used modeling, eleven (85%) conducted sensitivity analyses, six of which had one-way sensitivity analysis, whereas one conducted both one-way and two-way sensitivity analyses; four of these eleven modeling-based analyses included probabilistic sensitivity analyses. The incremental cost-effectiveness ratio was reported in ten (18%) studies, eight of which were screening studies. The remaining two modeling studies were in areas of imaging and oncology. Conclusion: This study indicates that there are major limitations and deficiencies in the health economic evaluations on medical devices performed in the People's Republic of China. Further efforts are required from different stakeholders – academic, governmental, and privatized – to improve health economic research capacity and to put it to use when informative decisions are made in the health care setting. Keywords: health economics, cost-effectiveness analysis, cost–utility analysis, cost–consequences analysis, medical devices, People's Republic of China